Study of overload effects in bainitic steel by synchrotron X-ray diffraction - P. Lopez-Crespo; P.J. Withers; J. R. Yates; A. Steuwer; T. Buslaps; Y. H. Tai (Fracture and Structural Integrity)
This work presents an in-situ characterisation of crack-tip strain fields following an overload by means of synchrotron X-ray diffraction. The study is made on very fine grained bainitic steel, thus allowing a very high resolution so that small changes occurring around the crack-tip were captured along the crack plane at the mid-thickness of the specimen. We have followed the crack as it grew through the overload location. Once the crack-tip has progressed past the overload event there is strong evidence that the crack faces contact in the region of the overload event (though not in the immediate vicinity of the current locations of the crack tip) at Kmin even when the crack has travelled 1mm beyond the overload location. It was also found that at Kmax the peak tensile strain ahead of the crack-tip decreases soon after the overload is applied and then gradually recovers as the crack grows past the compressive region created by the overload.